Accounting-Analytical and Evaluating Procedures for Defining the Economically Feasible Activities of the Oil Processing Enterprises of Kazakhstan - NURBAYEVA, Gulmira; SARTOVA, Rysty; ALSHYNBAY, Ainur; DUISEMALIYEVA, Madina; BULAKBAY, Zhanat (Journal of Advanced Research in Law and Economics; Vol 9 No 8 (2018): JARLE Volume IX Issue 8(38) Winter 2018DO - 10.14505//jarle.v9.8(38).19, 2019)
The issue of economic safety of an enterprise implying the security, control, insurance or modernization of the production is currently rather popular. So, the main objective of the paper is narrowed to the characteristics of the accounting-analytical and evaluating procedures for defining the economically feasible activities of the enterprises. The paper presents an analysis of the work of the oil processing enterprises in the territory of Kazakhstan. The novelty of the research is in the fact that due to the devaluation of the national currencies and the decrease in the cost of the oil barrel, a significant extent of the conducted and implemented operations has lost its economic sense. The paper notes that the feasibility of conducting particular financial-economic procedures should be estimated not by the strategical parameter, but also by the set of rules and tricks of the analytical and evaluating procedures. We defined the basic approaches to the evaluation of the attributes for conducting the economically feasible activities.